Mulheres vivenciando o estigma em decorrência da AIDS - Carvalho, Carolina Maria de Lima (2005)
It has been more than two decades that the world live with the HIV. Within the passing years we’ve learned a lot about ways of transmission, more efficient medical treatments, more accurate laboratory results, immunity, and so on. It’s still evident, however, the stigma experienced with the find out of the disease. That signalizes that the person is stamped and rejected. To carry a stigma means to carry a characteristic not accepted by society. Based on this fact, people live many prejudice situation and their chances of living naturally are reduced. That way, when a woman faces the positive HIV diagnostic she experiences uncertainty feelings and insecurity, those feelings lead her to a crisis moment. Taking all this into account, this work’s aim is to find out the stigmas that surround the women with HIV infection. This investigation is descriptive and exploratory and its nature is qualitative. The scenario is an infirmary of a specialized hospital in Fortaleza – CE .The research period was from December 2004 to March 2005. Ten women with positive HIV participated. The research method used was the Thematic Oral. It was used recorded semi-structured interview to collect data. The women’s reports were analyzed by creating four categories: 1) facing the diagnostic; 2) changes imposed by the disease; 3) guilt; and 4) living in social exclusion. The women were young, with scarce financial income; low scholar level and they were infected by heterosexual way. This profile coincides with the profile of the majority of infected women in Brazil. Many forms of stigma were identified. Most of them were related to the difficulty of dealing with the diagnostic, changes in the women’s lives because they tried to live better, guilt, social exclusion’s evidence and lack of family’s support. When they remembered the experience of receiving the diagnostic news, they expressed fear of death, shame, and concern with their family, abandonment, solitude, sadness and fault. Besides, they had to keep on trying not to loose their jobs. The different stigma that surround their lives don’t let them live naturally and free of any type of prejudice, and this is a right that has to be respected when we talk about women’s infected with the HIV, because they already suffer bad feelings caused by the disease. This work supported changes in the global assistance offered to infected women, emphasizing that the treatment shouldn’t concern only about biological-opportunists diseases, but should also consider the conflicts experienced by the women. That way, we search for an improvement in these women’s life quality. To defeat the stigmas and the prejudice is a task for all the professionals evolved with these women, this can be done by cultural or legal means.